The concise Oxford dictionary of English placenames - Ekwall, Eilert (Oxford : Clarendon Press, 1947)
Bibliotheek Camille Huysmans
Dedicator: van de Wijer, Jozef, dedicatee: Huysmans, Camille
Engels
Monografie
Keywords: toponymie